An Analysis of the Influence of Cultural Beliefs on Educational Leadership Practices in Pakistan: A Comparative Study of Public and Private Schools - Ali, Muhammad Sher Baz; Yasmeen, Razia (International Journal on Integrated Education, 2023)
Education is a key component of social and cultural development, and the influence of cultural beliefs on educational leadership practices cannot be overstated. This study focuses on the impact of cultural beliefs on educational leadership practices in Pakistan, with a specific emphasis on the comparison of public and private schools. The purpose of this study was to examine the influence of cultural beliefs on educational leadership practices in Pakistan and to compare the practices in public and private schools. The population of the study consisted of educational leaders in public and private schools in Pakistan. The sample of the study was selected through purposive sampling and consisted of 10 educational leaders in both public and private schools. In-depth interviews and observation were used as the primary data collection tools in this study. The data was analysed using a thematic analysis approach. The findings of this study revealed that cultural beliefs significantly influence educational leadership practices in Pakistan, particularly in terms of decision-making, communication, and relationship-building. It is recommended that further research be conducted to better understand the influence of cultural beliefs on educational leadership practices in different cultural contexts. Additionally, the results of this study can be used to inform the development of cultural competence training programs for educational leaders in Pakistan.